Aprendizagem, afetividade e cultura: uma análise da aula de língua alemã como língua adicional na educação infantil - Schmitt, Iasmin (Universidade do Vale do Rio dos Sinos, 2019)
The Teaching of Additional Languages in Early Childhood Education is still under development in Brazil, since it is a recent and growing practice. Some studies have focused on this teaching, seeking to understand the most diverse aspects related to the subject (e.g. SCHNACK, LEMKE, JAEGER, 2009; MACHADO, 2010). In this scenario, the studies are especially focused on the teaching of English Language in Early Childhood Education, since the growth of the offer of this teaching is greater in the English Language. To contribute to the area, and to foster discussions on the teaching of other languages, this research presents an analysis of German Language classes in a Kindergarten class in a city that is known for its Germanic descent. In order to do so, a qualitative research was carried out with an ethnographic bias (SILVEIRA, CÓRDOVA, 2009), whose data collection instruments included the observations of German Language classes and a semi-structured interview with the German Language teacher from the class. The observed school is located in the interior of the municipality of Nova Petrópolis. A Pre B Level class with 20 students was observed. The observed teacher uses methods developed by herself. The results show the organization of the German Language class, the presence of affection in learning through the Benni character and, finally, the presence of culture, whether global or local, in the Additional Language class, making possible the construction of links and the significance of these classes for children. Nevertheless, even if the German language class is interesting for the children, there are some points to be developed, such as providing a greater space of speech and interaction for children and personalization of these lines.
Keywords: Ensino de língua adicional na educação infantil; Afetividade na aprendizagem; Cultura no ensino de língua adicional; Additional language teaching in child education; Affectivity in learning; Culture in the teaching of additional language